2018
DOI: 10.1016/j.chembiol.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Lipid and Small-Molecule Modulation of COQ8 Reveals Regulation of the Ancient Kinase-like UbiB Family

Abstract: Human COQ8A (ADCK3) and Saccharomyces cerevisiae Coq8p (collectively COQ8) are UbiB family proteins essential for mitochondrial coenzyme Q (CoQ) biosynthesis. However, the biochemical activity of COQ8 and its direct role in CoQ production remain unclear, in part due to lack of known endogenous regulators of COQ8 function and of effective small molecules for probing its activity in vivo. Here, we demonstrate that COQ8 possesses evolutionarily conserved ATPase activity that is activated by binding to membranes c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 88 publications
1
81
2
Order By: Relevance
“…22,23 Our We propose that COQ9 acts as a lipid chaperone that helps to withdraw CoQ intermediates from the membrane and present them to soluble enzymes within complex Q. After Stefely et al, 19,20 Reidenbach et al, 21 and Lohman et al 24 structure of COQ9 unexpectedly revealed that it adopts an ancient TetR (tetracycline resistance) fold typically used by nutrient-sensing bacterial transcription factors [ Fig. 3(B)].…”
Section: Structural Genomicsmentioning
confidence: 88%
See 2 more Smart Citations
“…22,23 Our We propose that COQ9 acts as a lipid chaperone that helps to withdraw CoQ intermediates from the membrane and present them to soluble enzymes within complex Q. After Stefely et al, 19,20 Reidenbach et al, 21 and Lohman et al 24 structure of COQ9 unexpectedly revealed that it adopts an ancient TetR (tetracycline resistance) fold typically used by nutrient-sensing bacterial transcription factors [ Fig. 3(B)].…”
Section: Structural Genomicsmentioning
confidence: 88%
“…We propose that COQ9 acts as a lipid chaperone that helps to withdraw CoQ intermediates from the membrane and present them to soluble enzymes within complex Q. After Stefely et al, Reidenbach et al, and Lohman et al…”
Section: Finding Homes For the Orphansmentioning
confidence: 90%
See 1 more Smart Citation
“…Recent studies have revealed that ADCK3 lacks canonical protein kinase activity in the trans form; instead, it binds to lipid CoQ 10 intermediates and exhibits ATPase activity(Reidenbach, Kemmerer et al, 2018, Stefely et al, 2016). In the present study, GO analysis also revealed that interactors of ADCK4, especially in the mitochondria, are significantly associated with oxidoreductase activity, which can be related to the antioxidant property of CoQ 10 .…”
Section: Discussionmentioning
confidence: 99%
“…This observation has prompted speculation that Coq10 acts as a Q 6 chaperone protein required for delivery of Q 6 from its synthesis site to sites where Q 6 functions as an antioxidant and to the respiratory complexes, thereby bridging efficient de novo Q 6 biosynthesis with respiration (17). Recent studies have shown a spatial compartmentalization of the mitochondrial inner membrane with the identification of different sites, such as the inner boundary membrane, the cristae membrane, and the ER-mitochondrial contact sites (22)(23)(24)(25). Thus, for optimal respiratory competence, newly synthesized Q 6 must move from its site of synthesis (i.e.…”
mentioning
confidence: 99%